YOLO-R:road damage detector based on dynamic receptive fields and lightweight design - Mao, Jinghong; Wang, Mei; Liu, Zhenghong (Signal, image and video processing, 2025)
To address the challenges of missed detection, false detection, and low efficiency in road damage detection, this paper proposes an enhanced road damage detection model YOLO-R based on improved YOLOv8. First, we construct a collaborative module combining Switchable Atrous Convolution (SAC) with C2f. This module achieves precise multi-scale global feature extraction through dynamic adjustment of receptive fields. Second, an Adaptive Downsampling module (ADown) is designed to reduce computational complexity while maintaining feature representation capability. Furthermore, a Slim-neck module based on lightweight Group Shuffle Convolution (GSConv) and GSbottleneck is developed using VoV-GSCSP architecture to significantly improve feature fusion efficiency. Finally, the Shape-IoU bounding box regression loss function is introduced to improve localization accuracy through geometric prior optimization. Experiments on the cross-regional CRDDC2022 dataset (covering China and the US) demonstrate that YOLO-R achieves 76.3% mAP@0.50 while maintaining high inference speed, outperforming the baseline model by 3.7%. The model parameters and computational costs were reduced by approximately 12% and 33%, respectively. Comparative experiments confirm the model’s effectiveness and superiority in real-time road damage detection in complex scenarios.